ELECTRON-VOLT SPECTROSCOPY ON A PULSED NEUTRON SOURCE - Newport, R; Penfold, J; Williams, W (1984)
The principal design aspects of a pulsed source neutron spectrometer in which the scattered neutron energy is determined by a resonance absorption filter difference method are discussed. Calculations of the accessible dynamic range, resolution and spectrum simulations are given for the spectrometer on a high intensity pulsed neutron source, such as the spallation neutron source (SNS) now being constructed at the Rutherford Appleton Laboratory. Special emphasis is made of the advantage gained by placing coarse and fixed energy-sensitive filters before and after the scatterer; these enhance the inelastic/elastic discrimination of the method. A brief description is given of a double difference filter method which gives a superior difference peak shape, as well as a better energy transfer resolution. Finally, some first results of scattering from zirconium hydride, obtained on a test spectrometer, are presented.